瓜拉庇劳华人与辛亥革命 (The Chinese Of Kuala Pilah And The 1911 Revolution) - Goh, Wee Meng (2019)
The role of Singapore Chinese and Penang Chinese in the 1911 revolution is generally understood. That of Kuala Pilah Chinese, however, is scarcely known. How do Chinese gradually build a community in Kuala Pilah? How does Kuala Pilah Chinese react to 1911 revolution? What are the core movements of Kuala Pilah Chinese to support 1911 revolution? These are the principal questions that guide the analytical direction in this study. This study aims at providing a detail on the role of the Kuala Pilah Chinese in supporting the 1911 revolution in China. In order to interpret such a phenomenon, this study tends to adopt Tung Yen (Kuala Pilah local leader) as an example to reflect the support of Kuala Pilah Chinese for 1911 revolution. With the founding of the T’ung Meng Hui branch, Kuala Pilah Chinese are the main financial supporter to revolutionary activities, beside from supplying fund as well as offering refuge for revolutionaries abortive uprisings. Furthermore, this study will also deals with the scale of Kuala Pilah T’ung Meng Hui, the biography of T’ung Meng Hui’s member and the residence of Sun Yat-sen in Kuala Pilah. For methodology, this study will analyze and interpret archival documentation gathered from Malaysia, Singapore, Taiwan and others places. Besides that, field survey is also adopted in this study. Its goal is to unearth relic information from temple and memorial arch. Based on research findings，the reclamation of Chinese worker and the investment of Chinese Towkay are the two main causes of Kuala Pilah urbanization. Furthermore, Tung Yen is one of the Towkays who invests in Kuala Pilah. Due to the raising of political awareness, Tung Yen, a local leader recognized by British Colonial Government, decides to join revolutionary camp and enables the establishment of T’ung Meng Hui branch in Kuala Pilah. As a conclusion, Kuala Pilah Chinese has its own distinct uniqueness for being one of the main contributors in terms of fund for the various uprisings, and for the financial contribution to other revolutionary activities at a crucial time when response from other areas iv are still lacking not forthcoming. Lastly, the contribution of Kuala Pilah Chinese to the 1911 revolution is as important as all the other places.